Pembelajaran Berbasis Media Untuk Membangkitkan Semangat Belajar Siswa Siswi SD Negeri 01 Gintung Cilejet Dalam Mata Pelajaran Bahasa Indonesia - Raisa Maulida; Rizka Ayu Ramadanti; Fini Fajrini (BADAN PENERBIT STIEPARI PRESS, 2023)
The impact caused when the COVID-19 pandemic occurred resulted in learning program activities that had been implemented by schools in Indonesia using an online system. Therefore, this program was created to foster the development of effective teaching methods in increasing children's enthusiasm for learning by means of media-based learning. The government always renews the learning system through curricula that have been announced to various schools in Indonesia. Materially, students will get knowledge that is more flexible to follow the times, but many do not realize that children will feel bored and bored quickly in learning. This KKN program will develop innovations regarding learning using media such as using colorful cardboard, styrofoam, as well as several learning centers that are adjusted by the material to the media to be used. In addition, the system used in learning is a group consisting of 4 members, the aim is to build cohesiveness, socialization and a shared discussion space. Students are given the same task as given by the teacher, but the difference is using the media. Students are accompanied by members of KKN in carrying out the assigned tasks so that they understand and are directed in carrying out their duties. There are many students who are very active to find the right answer.